Integrated Plant Design for Green Hydrogen Production and Power Generation in Photovoltaic Systems: Balancing Electrolyzer Sizing and Storage - Alessandro Franco; Carlo Carcasci; Andrea Ademollo; Mattia Calabrese; Caterina Giovannini (Hydrogen)
This study evaluates the performance and feasibility of hybrid photovoltaic–hydrogen systems integrated with 4.2 MW PV installations, focusing on the interplay between electrolyzer capacity, energy storage, and hydrogen production. Key findings reveal that downsizing electrolyzers, such as using a 1 MW unit instead of a 2 MW model, increases operational efficiency by extending nominal power usage, though it reduces total hydrogen output by approximately 50%. Meanwhile, expanding energy storage systems show diminishing returns, with added capacity offering minimal gains in hydrogen production and raising economic concerns. The system’s performance is highly weather-dependent, with daily hydrogen production ranging from 26 kg on cloudy winter days to 375 kg during sunny summer conditions. Surplus energy export to the grid peaks at 3300 kWh during periods of high solar generation but is minimal otherwise. For economic and operational viability, the system design must prioritize directing a majority of PV energy to hydrogen production while minimizing grid export, requiring a minimum of 50% PV energy allocation to the hydrogen value chain. Cost analysis estimates a Levelized Cost of Hydrogen (LCOH) as low as €6/kg with an optimized configuration of a 2 MW electrolyzer and 2 MWh battery. Although high production costs challenge economic sustainability, careful component optimization and supportive policies can enable competitive hydrogen pricing and a positive net present value (NPV) over the system’s lifetime.